Evolution of the Presence and Engagement of Official Social Networks in Promoting Tourism in Spain - Sánchez Jiménez, Miguel Ángel; de Matos, Nelson; B. Correia, Marisol (Journal of Tourism, Sustainability and Well-being, 2019)
The recent growth in scale and relevance of social networks has generated new possibilities for communication and interaction with and among their users in the tourism sector. As Spain is among the world’s top tourism destinations, it is valuable to study its presence and engagement with users of official social networks. These social networks are used to promote Spain as a tourist destination. This study’s methodology focused on measuring a series of indicators of destination performance through the online analysis tool ‘Fanpage Karma’. Data were obtained for each of the last four full years (2015 to 2018), with the purpose of deepening understanding of destination performance, including its evolution. The findings show that Facebook’s importance increasingly declined, despite maintaining a large number of followers, it has seen reduced publications and, above all, less interactions with users. By contrast, Instagram has experienced continuous growth in promoting Spain as a tourist destination, demonstrating increasing levels of interaction with potential travellers. Implications for academia and industry are drawn from the findings.